Прогностичні напрями інформатизації професійної підготовки - Литвин, Андрій; Литвин, Оксана (Видавництво Львівської політехніки, 2018)
The author defines certain the most perspective of ICT, their possibilities are specified in relation to professional training in higher school, and also their specific is investigational in accordance with a didactic role in educational process.
Keywords: напрями інформатизації; професійна підготовка; комп’ютерно орієнтоване навчання; ІКТ